Making sense of communication interventions in public health emergencies – an evaluation framework for risk communication. (October 2015) - Dickmann, Petra; McClelland, Amanda; Gamhewage, Gaya M.; Portela de Souza, Patricia; Apfel, Franklin
Abstract : Communication interventions during public health emergencies (e.g. infectious disease outbreaks) are increasingly acknowledged as a determinant of success in preparedness, response and recovery. Challenges related to the current outbreak of Ebola virus in West Africa once again reveal the need to strengthen our understanding of the central importance and complexity of risk communication and social mobilisation strategies. There is little hard evidence, however, on the impact of various communication interventions upon the dynamics of public health emergencies to guide our capacity development. This article proposes a new evaluative framework which builds on an understanding of risk communication as an interactive, holistic, continuous and engaging activity that focuses on dialogue, intelligence gathering, building relationships over time with a knowledge base informed by new and accessible communication technologies (e.g. social media and networks) and supportive environments. Our hypothesis is that impact is measureable through the evaluation of identifiable performance parameters related to the dynamics of an outbreak. Our assumption is that risk communication interventions that lead to earlier detection, faster response, smoother coordination and a smarter legacy (ability to use processes and outcomes to improve current and future performance) lead to lower morbidity and mortality (reduced AUCepidemic curve ). This new evaluation framework for risk communication measures the relation between a baseline dynamic of epidemic and communication activities and the changed dynamic resulting from risk communication activities (e.g. earlier detection, faster response, smoother coordination and smarter legacy). We believe that a better understanding of how the two dynamics relate can lead to a better management of future public health emergencies.